1993
DOI: 10.1093/tropej/39.5.273
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemia: a Common Problem Among Uncomplicated Newborn Infants in Nepal

Abstract: Among a cross-sectional sample (stratified by weight and age after birth) of 226 uncomplicated term newborns from the delivery and postnatal wards of a busy government maternity hospital in Kathmandu, the period prevalence of hypoglycaemia (corrected blood glucose of < 2.6 mmol/l) during the first 50 hours after birth was 38 per cent. (This compares with a reported prevalence rate of 12 per cent from studies of uncomplicated term newborns in the UK.) Hypothermia, young maternal age, low birth weight and early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 0 publications
4
28
2
Order By: Relevance
“…14 Anderson et al also observed a high incidence of hypoglycemia in babies who were unfed (or) were delayed breast feeding upto 24 hours. 20 None of the infants who had low plasma glucose levels showed any clinical signs of hypoglycemia. However, the glucose level in all increased immediately after feed.…”
Section: Discussionmentioning
confidence: 94%
“…14 Anderson et al also observed a high incidence of hypoglycemia in babies who were unfed (or) were delayed breast feeding upto 24 hours. 20 None of the infants who had low plasma glucose levels showed any clinical signs of hypoglycemia. However, the glucose level in all increased immediately after feed.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, dextrose gel may also be useful in resource-poor settings where hypoglycemia is common and under diagnosed. 8,9,29 We have shown that dextrose gel is an effective, well tolerated and acceptable treatment for neonatal hypoglycemia. Dextrose gel should be considered for first line management of late preterm and term hypoglycemic babies in the first 48 hours after birth.…”
Section: Discussionmentioning
confidence: 99%
“…3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Uniform adoption and application of the standard WHO definition is fundamental to coordinated advancements in detection and management, but hypothermia continues to be variably defined, leading to under-recognition and under-reporting, and inadvertent denial of care to those who are misclassified but in need of care.…”
Section: Definitionmentioning
confidence: 99%
“…The incidence of primary hypothermiaFan independent morbidity that presents as a result of cold stressFis high immediately following birth in hospital settings. [11][12][13][14]16,20,[58][59][60] Few studies have addressed aspects surrounding the birth and postpartum care that can put the newborn at risk for hypothermia. 9,16,57,61 In one village-based study in India, 11% of 189 neonates were found to be hypothermic (<35.6 1C) based on a single temperature reading taken within the first 24 h after birth.…”
Section: Pathophysiology Of Neonatal Hypothermiamentioning
confidence: 99%